The control of hypertension in men and women: a comparative analysis - Stael Silvana Bagno Eleutério da Silva; Sofia de Fátima da Silva Barbosa de Oliveira; Angela Maria Geraldo Pierin (SciELO, 2016)
Abstract OBJECTIVE To compare men and women who have hypertension with reference to the following: high blood pressure, biosocial variables, habits and life styles, mental disorders, and social support networks. METHOD 290 hypertensive patients (women, 62.1%) were evaluated. The assessments involved the following: measuring blood pressure with an automatic measuring device, evaluating social status through the Social Support Scale, and the use of a Self-Report Questionnaire (SRQ-20) to identify common mental disorders. A value of p<0.05 was considered statistically significant. RESULTS Women were found to be different to men (p<0.05) in the following areas having: better control of their blood pressure (64.4% vs 52.7%), less salary incomes, less diabetes, higher total cholesterol, higher body mass index and wider abdominal circumferences. They also had lower systolic blood pressure, lower levels of alcohol consumption and a greater prevalence for mental disorders. The social support assessment revealed that hypertensive women received less help with preparing meals but had more company from people which allowed them to engage in enjoyable activities. CONCLUSION Women had more control over their blood pressure than men, despite the presence of negative biopsychosocial factors that may have influenced their adherence to the treatments.